Profile of Plasma Amino Acid Levels in Rats Exposed to Acute Hypoxic Hypoxia - Muratsubaki, Haruhiro (Springer-Verlag, 2011)
The effect of acute hypoxic hypoxia on the profile of plasma amino acids in rats was studied and compared to that resulting from acute liver injury induced by giving carbon tetrachloride. In hypoxic rats exposed to 45% air in N(2) for 5 h, the concentrations of branched chain amino acids, including valine, leucine and isoleucine, and aromatic amino acids such as phenylalanine and tyrosine were significantly increased as compared to those in normoxic rats. The ratio of branched-chain to aromatic amino acids (Fischer’s ratio) was significantly decreased. The levels of arginine and citrulline, which are related to the urea cycle, were also depressed. Furthermore, plasma proline level was reduced in hypoxic rats. The activities of plasma marker enzymes for tissue damage remained unchanged during hypoxia, indicating that tissue injury was not induced by exposure to hypoxic conditions. We suggest that the characteristic profile of plasma amino acids and the Fischer ratio are valuable tools for understanding the pathology of acute hypoxia in the absence of systemic tissue damage.